Carbon nanotube with enhanced surface wettability and preparation method thereof
By forming a silicon carbide layer in situ on the surface of the carbon nanotubes, the problems of poor compatibility and agglomeration in the composite materials are solved, and the surface wetting and compatibility of the composite materials are enhanced, and the performance and production efficiency of the composite materials are improved.
Patent Information
- Application Number
- CN202411686293.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-04
AI Technical Summary
In applications, carbon nanotubes have problems such as few surface defects, low solubility, poor dispersion performance and poor compatibility with other materials, making it difficult to effectively add composite materials with excellent properties as reinforced phases.
By forming a silicon carbide layer in situ on the surface of the carbon nanotube, mixing silicon powder and carbon nanotubes using high-energy ball milling technology, and then sintering at high temperature in a vacuum state to generate a 10-50nm-thick silicon carbide layer.
The surface wettability of carbon nanotubes is enhanced, its compatibility with other materials is improved, agglomeration is avoided, and the mechanical properties and production efficiency of composite materials are improved.
Smart Images

Figure CN119750558A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon nanotubes, in particular to a carbon nanotube with enhanced surface wettability and a preparation method thereof. Background Art
[0002] Carbon nanotubes have superb mechanical properties, extremely high aspect ratios and unique electrical conductivity, making them an ideal form for preparing composite materials. However, carbon nanotubes have few surface defects, lack active groups, have low solubility in various solvents, and have poor dispersion and compatibility with other materials. In addition, there is a strong van der Waals attraction between carbon nanotubes, and their huge specific surface area and high aspect ratio cause them to form agglomerations or entanglements, which seriously affects their application.
[0003] The Chinese patent document with publication number CN103242684B discloses a silicon dioxide-coated carbon nanotube and a preparation method thereof, wherein the preparation method comprises the following steps: mixing carbon nanotubes, surfactants, anhydrous ethanol and deionized water in a mass ratio of 1:0.5-2:70-90:10-30, adjusting the pH to 8-9.5, and obtaining a first mixed solution; mixing tetraalkoxy silicon and anhydrous ethanol in a mass ratio of 1:10-30, and then dropping them into the first mixed solution at 25°C-60°C, and fully reacting them under stirring to obtain a second mixed solution; dropping a silane coupling agent into the second mixed solution, and fully reacting them under stirring, and obtaining the silicon dioxide-coated carbon nanotube after separation and purification. Compared with the traditional preparation method of silicon dioxide-coated carbon nanotubes, this preparation method of silicon dioxide-coated carbon nanotubes does not require acidification of carbon nanotubes, and does not destroy the structure of carbon nanotubes. However, the preparation of the mixed solution required by this method is complicated and costly, and is only applicable to the laboratory stage, not suitable for industrial production.
[0004] The Chinese patent document with publication number CN109311672A discloses a carbon nanotube dispersion with improved processability and a preparation method thereof. The preparation method comprises the following steps: by dry-grinding carbon nanotubes to control the wettability index of carbon nanotubes, the maximum concentration of carbon nanotubes that can be added to the dispersion solvent can be increased, and the processability of the carbon nanotube dispersion can be improved. In addition, by applying the above-mentioned characteristics, the maximum concentration of carbon nanotubes that can be added to the dispersion solvent can be easily predicted. However, in the early stage of this method, by dry-grinding carbon nanotubes, the carbon nanotubes will be severely fragmented and have no complete structure, which affects the performance of the carbon nanotubes.
[0005] Therefore, there is still a lack of a carbon nanotube with enhanced surface wettability and a preparation method thereof, which can achieve industrial production while ensuring the structural integrity of the carbon nanotube. Summary of the invention
[0006] The purpose of the present invention is to provide a carbon nanotube with enhanced surface wettability and a preparation method thereof, which effectively solves the problem that the carbon nanotube itself has poor compatibility with other materials, is easy to form agglomerates, and is difficult to add alone as a reinforcing phase to prepare a composite material with excellent performance. The method enables carbon nanotubes to have broad application prospects in the field of material science and has high industrial production value.
[0007] To achieve this object, the present invention designs a carbon nanotube with enhanced surface wettability, including a complete carbon nanotube and a silicon carbide layer, wherein the surface of the complete carbon nanotube is coated with a silicon carbide layer, and the silicon carbide layer is generated by an in-situ reaction of broken carbon nanotubes and silicon powder on the surface of the complete carbon nanotube (silicon carbide is generated in situ on the surface of the carbon nanotube by chemical bonding, and the bonding force is stronger).
[0008] The thickness of the silicon carbide layer is in the range of 10 to 50 nm. The silicon carbide layer can effectively block the van der Waals force between the carbon nanotubes. If the thickness is less than 10 nm, the dispersion effect is poor, and if the thickness is greater than 50 nm, the carbon nanotubes cannot play a good strengthening role.
[0009] A method for preparing carbon nanotubes with enhanced surface wettability comprises the following steps:
[0010] Step 1: In a vacuum state, silicon powder and carbon nanotubes are ball-milled and mixed using high-energy ball milling technology (the ball milling process has a high energy density and can break up large carbon nanotube agglomerates) to form a mixed powder of broken carbon nanotubes and silicon powder required for the in-situ reaction of silicon carbide;
[0011] Step 2, adding intact carbon nanotubes to the mixed powder of the broken carbon nanotubes and silicon powder to perform secondary ball milling and mixing, so that the broken carbon nanotubes and silicon powder are evenly distributed on the surface of the intact carbon nanotubes;
[0012] Step 3, sintering the secondary mixed powder at high temperature under vacuum conditions, so that the broken carbon nanotubes and silicon powder react in situ on the surface of the intact carbon nanotubes to generate silicon carbide (carbon and silicon can react to generate silicon carbide at high temperatures, and experiments have shown that the broken carbon nanotubes are more likely to react with silicon than the intact carbon nanotubes), and finally preparing a carbon nanotube with enhanced surface wettability.
[0013] In the above step 1, vacuum high-energy ball milling technology is a powder processing method that uses high-speed rotating ball milling media to strongly impact and rub silicon powder and carbon nanotubes under a vacuum environment. During the ball milling process, the ball milling media continuously impacts and rubs silicon powder and carbon nanotubes under the centrifugal force of high-speed rotation, causing the silicon powder and carbon nanotubes to be broken, refined, and mixed. This technology can achieve efficient material processing in a short time while keeping the chemical composition and physical properties of silicon powder and carbon nanotubes unchanged. At the same time, vacuum high-energy ball milling technology can increase the contact area between carbon nanotubes and silicon powder, which is conducive to the direct reaction between the two.
[0014] In the above step 3, a silicon carbide layer is formed on the surface of the carbon nanotube, which avoids the generation of carbon nanotube agglomeration phenomenon and solves the problem of poor compatibility between carbon nanotubes and other materials (carbon nanotubes themselves are incompatible with the matrix material, and serious agglomeration will lead to increased defects and reduced performance). There is a strong van der Waals force between two adjacent carbon nanotubes, which is easy to form agglomeration phenomenon. The silicon carbide layer is coated on the surface of the carbon nanotube, which avoids the entanglement between the carbon nanotubes and forms a stable dispersion state. The surface wettability of silicon carbide is better than that of carbon nanotubes. Wrapping on the surface of carbon nanotubes can reduce the direct contact between carbon nanotubes and other materials. Silicon carbide has good wettability with aluminum, while pure carbon nanotubes have poor wettability with aluminum. Therefore, growing a layer of silicon carbide on the surface of carbon nanotubes can greatly improve the wettability with aluminum, which is more conducive to the interface bonding between the two and is conducive to the addition of carbon nanotubes to aluminum liquid.
[0015] In the above technical solution, silicon powder and carbon nanotubes are ball-milled and mixed under vacuum, and the molar ratio of silicon powder to carbon nanotubes is 1:0.5 to 2, preferably 1:1. Carbon and silicon react completely at a molar ratio of 1:1. Below this ratio, more broken carbon nanotubes remain, and the strengthening effect is poor. Above this ratio, the residual silicon will react with the complete carbon nanotubes, which may destroy their structure.
[0016] In step 1 of the above technical solution, the ball milling time of silicon powder and carbon nanotubes is 4 to 12 hours under vacuum. If the ball milling time is less than 4 hours, the carbon nanotubes are not completely broken and cannot be fully mixed; if the ball milling time exceeds 12 hours, the powder breaking state does not change much and the efficiency is low.
[0017] In step 1 of the above technical solution, the vacuum degree ranges from -10 to 0.5 Pa. Below -10 Pa, the air content is already extremely low; above 0.5 Pa, silicon is easily oxidized.
[0018] In step 1 of the above technical solution, the particle size of the silicon powder for ball milling is 50nm-13μm, and the carbon nanotubes are multi-walled carbon nanotubes. The use cost of single-walled carbon nanotubes is extremely high, and it is very difficult to disperse single-walled carbon nanotubes in resin. The conventional means of dispersing single-walled carbon nanotubes cannot achieve satisfactory results. Multi-walled carbon nanotubes are relatively low in cost, suitable for industrial production, and have a more easily dispersed effect. The diameter of the carbon nanotubes is 10-200nm, and the length of the carbon nanotubes is 5-20μm. Carbon nanotubes with too large an aspect ratio are not easy to disperse, and carbon nanotubes with too small an aspect ratio do not improve the performance of aluminum alloy materials as well as carbon nanotubes with long aspect ratios. The smaller the particle size of the silicon powder, the more uniform the crushing and mixing of carbon nanotubes and silicon powder, but the cost is also more expensive, which is not conducive to actual production applications.
[0019] In step 2 of the above technical solution, the volume ratio of the complete carbon nanotubes to the mixed powder of the broken carbon nanotubes and silicon powder is 1:0.5 to 3. This ratio can ensure that the in-situ generated silicon carbide can be completely coated on the surface of the carbon nanotubes. Below this range, there are fewer complete carbon nanotubes and the strengthening effect is not ideal. Above this range, due to the small proportion of silicon carbide, the uncoated carbon nanotubes will still have serious agglomeration.
[0020] In step 2 of the above technical solution, complete carbon nanotubes are added to the mixed powder of the broken carbon nanotubes and silicon powder for secondary mixing, which is short-time ball milling mixing. The ball milling time for short-time ball milling mixing is 0.5 to 4 hours. If the ball milling time is less than 0.5 hours, the powder in step 1 cannot be completely and evenly distributed on the surface of the carbon nanotubes; if the time exceeds 4 hours, the structure of the newly added carbon nanotubes will be destroyed, and the strengthening effect will decrease. Short-time ball milling can ensure that the complete carbon nanotube structure is not destroyed while mixing evenly. The long-time mixing in step 1 is to obtain completely mixed silicon and broken carbon nanotubes. After the carbon nanotubes are broken, the contact area with the silicon powder becomes larger and it is easier to react; the short-time mixing in step 2 is to ensure that the structure of the carbon nanotubes added for the second time is not destroyed while enabling it to be effectively mixed evenly.
[0021] In the above technical solution, the vacuum degree when the above-mentioned secondary mixed powder is sintered in a vacuum state is -15 to 0.5Pa. The vacuum degree of -15 to 0.5Pa can ensure that silicon will not be oxidized to form silicon dioxide. Below -15Pa, the air content is already extremely low; above 0.5Pa, silicon is easily oxidized. Silicon powder is the main raw material for in-situ reaction to generate silicon carbide. After reacting on the surface of carbon nanotubes, it can be tightly wrapped on the surface of carbon nanotubes, and the generated silicon dioxide cannot achieve the effect of tight coating.
[0022] In the above technical solution, the vacuum sintering temperature when the above secondary mixed powder is sintered in a vacuum state is 1000° C. to 1400° C. In this temperature range, carbon and silicon can react to produce silicon carbide. If the temperature is too low, the two cannot react, and if the temperature is too high, it will cause a waste of resources.
[0023] In the above technical solution, the sintering time of the above secondary mixed powder in a vacuum state is 1 to 5 hours. Too short a time will lead to incomplete reaction between carbon and silicon, which will result in less silicon carbide coated on the surface of the carbon nanotubes, poor wettability of the uncoated carbon nanotubes, and serious agglomeration. If the time exceeds 5 hours, the efficiency will be low. The reaction of carbon and silicon is relatively complete within 5 hours. Too long a time is not conducive to industrial production and has low efficiency.
[0024] Beneficial effects of the present invention:
[0025] 1. Through high-energy ball milling combined with high-temperature sintering technology, the effect of coating the surface of carbon nanotubes with a silicon carbide layer can be achieved, thereby enhancing the surface wettability of carbon nanotubes. During the metallurgical crystallization process, if the interface tension between the impurities in the melt and the grains is small, the contact angle θ is small, and the wettability is good. The crystal nuclei will spread on the impurities, and the crystallization process will be promoted with the impurities as the center, which will help to refine the grains and improve and enhance the mechanical properties of the metal. The interface wettability between silicon carbide and other materials is much better than that of carbon nanotubes. As an intermediate medium, it can effectively prevent carbon nanotubes from directly contacting other materials.
[0026] 2. The silicon carbide layer is prepared on the surface of carbon nanotubes, which effectively solves the problem of light specific gravity and easy agglomeration of carbon nanotubes when used as the reinforcing phase of composite materials; silicon carbide is coated on the surface of carbon nanotubes by chemical reaction and is tightly combined. The density of silicon carbide is much greater than that of carbon nanotubes. The silicon carbide layer is coated on the surface of carbon nanotubes, which avoids entanglement between carbon nanotubes and stabilizes the dispersion state.
[0027] 3. The crushed carbon nanotubes in the present invention are used to provide the carbon required for the formation of silicon carbide. After crushing, the mixture is evenly mixed and is easier to react. The complete carbon nanotubes added for the second time are used as a reinforcement phase.
[0028] 4. The production efficiency of silicon carbide-coated carbon nanotubes has been greatly improved, which has practical production value;
[0029] 5. The process of the present invention is simple to operate, can be prepared in batches, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:
[0032] Example 1
[0033] like Figure 1 The carbon nanotube with enhanced surface wettability and the preparation method thereof include the following steps:
[0034] Step 1: Under a vacuum state of -0.1 Pa, a planetary ball mill is used to mix silicon powder with a particle size of 500 nm and multi-walled carbon nanotubes with a diameter of 20 nm and a tube diameter of 15 μm. The molar ratio of silicon powder to carbon nanotubes in the ball milling is 1:1. The ball milling time is 10 hours to form a mixed powder of broken carbon nanotubes and silicon powder required for the in-situ reaction of silicon carbide;
[0035] Step 2: adding intact carbon nanotubes in a volume ratio of 1:1 to the mixed powder of the crushed carbon nanotubes and silicon powder for secondary ball milling, and taking out a uniform mixed powder after ball milling for 1 hour;
[0036] Step 3: Sintering at a vacuum degree of -5 Pa and a temperature of 1250°C for 2 hours allows the broken carbon nanotubes and silicon powder to react in situ on the surface of the intact carbon nanotubes to generate silicon carbide. The thickness of the silicon carbide layer is 30nm, and finally a carbon nanotube with enhanced surface wettability is obtained.
[0037] Example 2
[0038] This embodiment is basically the same as Embodiment 1, except that the particle size of the silicon powder in Step 1 is 50 nm.
[0039] Example 3
[0040] This embodiment is basically the same as Embodiment 1, except that the particle size of the silicon powder in Step 1 is 800 nm.
[0041] Example 4
[0042] This embodiment is basically the same as Embodiment 1, except that the particle size of the silicon powder in Step 1 is 13 μm.
[0043] Example 5
[0044] This embodiment is basically the same as embodiment 1, except that the ball milling time in step 1 is 4 hours.
[0045] Example 6
[0046] This embodiment is basically the same as embodiment 1, except that the ball milling time in step 1 is 8 hours.
[0047] Example 7
[0048] This embodiment is basically the same as embodiment 1, except that the ball milling time in step 1 is 12 hours.
[0049] Example 8
[0050] This embodiment is basically the same as the embodiment 1, except that in the step 2, the volume ratio of the intact carbon nanotubes to the mixed powder of the broken carbon nanotubes and silicon powder is 1:3.
[0051] Example 9
[0052] This embodiment is basically the same as the embodiment 1, except that in the step 2, the volume ratio of the intact carbon nanotubes to the mixed powder of the broken carbon nanotubes and silicon powder is 1:2.
[0053] Example 10
[0054] This embodiment is basically the same as the embodiment 1, except that in the step 2, the volume ratio of the intact carbon nanotubes to the mixed powder of the broken carbon nanotubes and silicon powder is 1:0.5.
[0055] Embodiment 11
[0056] This embodiment is basically the same as the embodiment 1, except that in the step 2, the complete carbon nanotubes are added to the mixed powder of the crushed carbon nanotubes and silicon powder for secondary ball milling and the mixing time is 0.5 hours.
[0057] Example 12
[0058] This embodiment is basically the same as the embodiment 1, except that in the step 2, complete carbon nanotubes are added to the mixed powder of the crushed carbon nanotubes and silicon powder for secondary ball milling for 2 hours.
[0059] Embodiment 13
[0060] This embodiment is basically the same as the embodiment 1, except that in the step 2, complete carbon nanotubes are added to the mixed powder of the crushed carbon nanotubes and silicon powder for secondary ball milling for 4 hours.
[0061] Embodiment 14
[0062] This embodiment is basically the same as Embodiment 1, except that the sintering vacuum degree in step 3 is -15Pa.
[0063] Embodiment 15
[0064] This embodiment is basically the same as Embodiment 1, except that the sintering vacuum degree in step 3 is -10Pa.
[0065] Example 16
[0066] This embodiment is basically the same as Embodiment 1, except that the sintering vacuum degree in step 3 is 0.5 Pa.
[0067] Embodiment 17
[0068] This embodiment is basically the same as embodiment 1, except that the sintering temperature in step 3 is 1000°C.
[0069] Embodiment 18
[0070] This embodiment is basically the same as embodiment 1, except that the sintering temperature in step 3 is 1200°C.
[0071] Embodiment 19
[0072] This embodiment is basically the same as embodiment 1, except that the sintering temperature in step 3 is 1400°C.
[0073] Embodiment 20
[0074] This embodiment is basically the same as Embodiment 1, except that the sintering time in step 3 is 1 hour.
[0075] Embodiment 21
[0076] This embodiment is basically the same as Embodiment 1, except that the sintering time in step 3 is 3 hours.
[0077] Embodiment 22
[0078] This embodiment is basically the same as Embodiment 1, except that the sintering time in step 3 is 5 hours.
[0079] The interface contact angle between the silicon carbide coated carbon nanotube composite material and the aluminum droplet obtained in Examples 1 to 22 was tested. The test method was to pressurize the silicon carbide coated carbon nanotube composite material into a block at room temperature, pour pure aluminum melt on a specially designed iron mesh support, and filter the oxide layer naturally formed on the outer surface of the Al droplet in a vacuum. Under a vacuum of 800°C, pure liquid aluminum droplets were precipitated on the surface of the composite material for 5 minutes. An optical camera was used to characterize the contact angle of the interface between the Al droplet and the composite material. The test results are shown in Table 1. The wetting performance of the liquid on the surface of the solid material is measured by the contact angle of the liquid on the surface of the solid material.
[0080] Table 1 Comparison of interface contact angles of Examples 1 to 22
[0081]
[0082]
[0083] It can be seen from the data in the table that a series of tests were carried out on seven parameters, namely, the time of the first ball milling, the particle size of the silicon powder, the time of the second ball milling, the proportion of the carbon nanotubes added for the second time, the vacuum degree of high-temperature sintering, the high-temperature sintering temperature and the time of high-temperature sintering. After the interface contact angle test with the aluminum droplet, the first ball milling time adopted in Example 1 was 10 hours, the particle size of the silicon powder was 500nm, the diameter of the multi-walled carbon nanotubes was 20nm, the diameter of the multi-walled carbon nanotubes was 15μm, the time of the second ball milling was 1 hour, the proportion of the carbon nanotubes added for the second time was 1:1, the vacuum degree of high-temperature sintering was -5Pa, the high-temperature sintering temperature was 1250℃, the high-temperature sintering time was 2 hours, and the thickness of the silicon carbide layer was 30nm as the optimal process parameters. The interface contact angle between the prepared silicon carbide-coated carbon nanotube composite material and the aluminum droplet was 128.3°, which improved the compatibility between the carbon nanotubes and the aluminum matrix.
[0084] The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. A carbon nanotube with enhanced surface wettability, characterized in that: It comprises complete carbon nanotubes and silicon carbide layers, wherein the surface of the complete carbon nanotubes is covered with the silicon carbide layer, and the silicon carbide layer is generated by in-situ reaction of broken carbon nanotubes and silicon powder on the surface of the complete carbon nanotubes.
2. The carbon nanotube with enhanced surface wettability according to claim 1, characterized in that: The thickness of the silicon carbide layer is in the range of 10 to 50 nm.
3. A method for preparing carbon nanotubes with enhanced surface wettability, characterized in that: The steps include: In a vacuum state, silicon powder and carbon nanotubes are ball-milled and mixed to form a mixed powder of broken carbon nanotubes and silicon powder required for an in-situ reaction of silicon carbide; adding intact carbon nanotubes to the mixed powder of the crushed carbon nanotubes and silicon powder for secondary mixing; The secondary mixed powder is sintered in a vacuum state, so that the broken carbon nanotubes and silicon powder react in situ on the surface of the intact carbon nanotubes to generate silicon carbide.
4. The method for preparing carbon nanotubes with enhanced surface wettability according to claim 1, characterized in that: In a vacuum state, silicon powder and carbon nanotubes are ball-milled and mixed, wherein the molar ratio of silicon powder to carbon nanotubes is 1:0.5 to 2 。 5. The method for preparing carbon nanotubes with enhanced surface wettability according to claim 1, characterized in that: The silicon powder and the carbon nanotubes are ball-milled and mixed under vacuum for 4 to 12 hours.
6. The method for preparing carbon nanotubes with enhanced surface wettability according to claim 1, characterized in that: The particle size of the silicon powder for ball milling is 50nm-13μm, the carbon nanotube is a multi-walled carbon nanotube, the diameter of the carbon nanotube is 10-200nm, and the length of the carbon nanotube is 5-20μm.
7. The method for preparing carbon nanotubes with enhanced surface wettability according to claim 1, characterized in that: The volume ratio of the added complete carbon nanotubes to the mixed powder of the broken carbon nanotubes and silicon powder is 1:0.5-3.
8. The method for preparing carbon nanotubes with enhanced surface wettability according to claim 1, characterized in that: The complete carbon nanotubes are added to the mixed powder of the broken carbon nanotubes and silicon powder for secondary mixing, which is short-time ball milling mixing. The ball milling time of the short-time ball milling mixing is 0.5 to 4 hours.
9. The method for preparing carbon nanotubes with enhanced surface wettability according to claim 1, characterized in that: The vacuum degree when the powder after the secondary mixing is sintered in a vacuum state is -15 to 0.5 Pa.
10. The method for preparing carbon nanotubes with enhanced surface wettability according to claim 1, characterized in that: The vacuum sintering temperature when the secondarily mixed powder is sintered in a vacuum state is 1000° C. to 1400° C., and the sintering time when the secondarily mixed powder is sintered in a vacuum state is 1 to 5 hours.
Citation Information
Patent Citations
Silica-coated carbon nanotubes and their preparation methods
CN103242684B
Carbon nanotube dispersion with improved workability and preparation method therefor
CN109311672A
Silicon carbide coating modified multi-walled carbon nanotube reinforced silicon-boron-carbon-nitrogen ceramic composite material and preparation method thereof
CN108503384A
Method for fabrication of si coated multi-wall carbon NANO tube for composite materials
KR1020120021376A
Training object detection systems with generated images
KR1020230001524A